Mecanisme ale inovaţiei în asistenţa socială - Arpinte, Daniel (Calitatea Vieții, 2009)
The article presents the role of innovation in designing new models of social intervention, and its impact in the process of institutional development. The first part analyses the factors which encouraged a high level of innovation in Romanian social services system, the main sources of innovation and the key stages of its dynamics. In the second part the main types of innovation are presented, being analysed relevant cases for each of them.